Stoichiometric Plant-Herbivore Models and Their Interpretation - Yang Kuang; Jef Huisman; James J. Elser (Mathematical Biosciences and Engineering)
The purpose of this note is to mechanistically formulate amathematically tractable model that specifically deals with thedynamics of plant-herbivore interaction in a closedphosphorous (P) limiting environment. The key to our approach isthe employment of the plant cell P quota and the Droopequation for its growth. Our model takes the simple form of asystem of two autonomous ordinary differential equations. It canbe shown that our model includes the LKE model (Loladze, Kuang and Elser (2000)) as a special case. Our study reveals that the details of ecological stoichiometry models really matter for quantitativepredictions of plant-herbivore dynamics, especially atintermediate ranges of the carrying capacity.